Factors affecting undergraduate nursing students’ professional commitment: a structural equation modeling analysis - Guo-Cui Wu; Yu-Ye Zuo; Bin-Bin Feng; Zi-Ye Liu; Yan-Qin Zhu; Lin Zhu (BMC Nursing)
Abstract Background Previous research has demonstrated that nursing students’ professional commitment is less than ideal. However, a clear theoretical model to explain or mediate the factors influencing their professional commitment is currently lacking. Building on Social Cognitive Theory (SCT), this study aimed to describe the current situation regarding the professional commitment of undergraduate nursing students and examine its relationships with psychological resilience, medical education environment, innovation ability, and self-directed learning ability. Methods A total of 813 undergraduate nursing students were recruited through convenience sampling for a cross-sectional study at a medical university in Anhui province. Participants completed the General Information Questionnaire, Professional Commitment Scale, Innovation Ability Scale, Self-Directed Learning Ability Scale, Psychological Resilience Scale, and Dundee Ready Educational Environment Measure (DREEM). Structural equation modeling was used to analyze the hypothesized relationships. Results Nursing students’ total professional commitment score averaged 93.36 ± 13.63. Medical education environment, self-directed learning ability, and innovation ability all significantly and directly associated with professional commitment (β = 0.294, β = 0.167, β = 0.358, respectively). Self-directed learning and innovation ability mediated the effects of psychological resilience (β = 0.114, 0.054, respectively) and the medical education environment (β = 0.089, 0.063, respectively) on professional commitment. Additionally, self-directed learning and innovation ability exhibited a significant chain mediating effect between psychological resilience and the influence of medical education environment on professional commitment (β = 0.114, 0.054, respectively). Conclusions Our study reveals that self-directed learning and innovation ability mediate the effects of psychological resilience and educational environment on nursing students’ professional commitment.These findings suggest nursing educators could focus on fostering students’ self-directed learning abilities in teaching and enhancing students’ professional commitment by optimizing the educational environment and strengthening mental toughness training.